Nanoparticle albumin-bound paclitaxel combined with cisplatin as the first-line treatment for metastatic esophageal squamous cell carcinoma - Shi, Yan (Dove Medical Press, 2013)
Esophageal cancer is a major health hazard in many parts of the world and is often diagnosed late. The objective of this study was to explore the efficacy and safety of nanoparticle albumin-bound paclitaxel (Nab-PTX) combined with cisplatin (DDP) in patients with metastatic esophageal squamous cell carcinoma (ESCC). Patients with histologically confirmed ESCC were treated with Nab-PTX 250 mg/m(2) and DDP 75 mg/m(2) intravenously on day 1, every 21 days. Evaluation was performed after every two cycles of therapy and the therapy was continued until disease progression or unacceptable toxicity. From April 2010 to December 2012, 33 patients were enrolled. Ten patients had recurrent and metastatic tumors after surgery and 23 patients were diagnosed with unresectable metastatic disease. Patients received a median of four cycles of therapy (ranging from two to six cycles). Twenty patients achieved partial response and nine patients achieved stable disease; no complete response was observed. The objective response rate was 60.6% and the disease control rate was 87.9%. The median progression-free survival was 6.2 months (95% confidence interval: 4.0 to 8.4 months) and the median overall survival was 15.5 months (95% CI: 7.6 to 23.4 months). Only four patients experienced grade 3 adverse events, including vomiting, neutropenia, and sensory neuropathy. The most common adverse events were nausea/vomiting (81.8%), neutropenia (63.6%), leucopenia (48.5%), anemia (24.2%) and sensory neuropathy (24.2%). In conclusion, the combination of Nab-PTX and DDP is a highly effective and well-tolerated first-line treatment in metastatic ESCC.